REFORMULASI PENDIDIKAN ISLAM DALAM KELUARGA - Sopiah * (Jurnal Forum Tarbiyah, 2010)
Education by parents to their children in the family has a very important position, especially in modern times as present, where external influence is very heavy and diverse. Our children are much influenced by both positive and negative influences. Lastly, the worrying effect at this goge era, the influence of electronic, printed and communication media is very influential on the development of children, moreover those means are more sophisticated, faster and easier. Our children can learn, access and search for any information easily. Meanwhile parents do not have a free opportunity to educate, guide and direct them, then it is the time for parents to realize it, turn to the belief that education in the family is important, should be prioritized for our children’s optimal development purposes in terms of the formation of perfect beings.